(3OjhGf eMeO Hf CejQ GdMGLs - (3eMeO Hf eMeO Hf eMeO Hf CejQ MGL GHf GdeDbJ ,GHf GejQ MGL , TeS GdOjf CHh YHO Gddg,J (B879 (3g` s
(3ChdgG (B:s
(3CMeO QHG YOO GdSfjfG YdefG ddPcQ Ef fSjfG eUdjkG Ydi QShd TeNkG YdGg aj GdhLhO cj jDQNG s
(3BNQgG (B:s
(3HZjQ CmN Hg deG XaQfG CJi JGQjNg XaQ jJje s
(3GfXQg eY OjhGf Ydj GdYGedjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B49 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B274 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B208s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B200 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHIBjI Gddg GdMcje GdYGeI (B- (3GdfLa (B(745) s
Keywords: (3GdCOHs